HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN MINUM OBAT ANTI TB PADA PASIEN TB PARU DI PUSKESMAS X KOTA BANDUNG - Nabilah Nur Jannah; Nandang Ahmad Waluya; Anah Sasmita; Asep Setiawan (Jurnal Keperawatan Indonesia Florence Nightingale, 2022)
This research is motivated by the high TB ​​incidence rate in Indonesia and the success rate of treatment in West Java which has not reached the 88% target. Family support is important because it is an effort to improve medication adherence. This study aims to determine the relationship of family support with adherence to taking anti-TB drugs (OAT) in pulmonary TB patients. Analysis of the data used is bivariate analysis using the Chi-Square statistical test. Family support research results show that there are 13 people (44.8%) who support and 16 people (55.2%) do not support, and compliance shows that there are 20 people (69%) high adherence and 9 people (31%) low adherence. There is no relationship between family support with adherence to taking anti-TB drugs (OAT) in patients with pulmonary TB with a p value of 0.688 (α = 0.05). It is recommended for nurses to increase their promotive efforts by providing information and Health Education about the effects of tuberculosis treatment that is not complete and always reminds their families to motivate TB patients to not forget to take medication.